The benefits of latent payback in social dilemmas - Andreas Glöckner; Sebastian Kube; Andreas Nicklisch (Verein für Socialpolitik, 2010)
Latent payback is a natural element of social interactions: Non-cooperators face substantial threats of not being supported in situations of dire need, or of being punished in seemingly unrelated situations. In the controlled environment of the laboratory, we experimentally explore the effects of latent sanctions on cooperation per se, as well as on the effectiveness of immediate sanctions. Our data indicate that latent sanctions alone are able to sustain cooperation in groups. However, the real power of latent sanctions is unleashed when combined with immediate sanctions. These situations enormously enhance cooperation within groups - and, do so moreover, with less intense sanctioning. This surprising result provides a potential explanation for the co-existence of latent and immediate sanctions in social interactions.
Keywords: C92; H41; K00; 330; Decentralized Punishment; Latent Sanctions; Public Goods; Sanctioning Effectiveness; Voluntary Contribution Mechanism; Laboratory Experiment